Village Pay Phones and Poverty Reduction: Insights from a Grameen Bank Initiative in Bangladesh - A. Bayes, J. von Braun, R. Akhter (ZEF - Discussion Papers on Development Policy 8, 1999)
The intent of the present study is to evaluate the role of telecommunications within the contexts of rural development in general and of poverty reduction in particular. Bangladesh has been selected as a case study due to the uniqueness it displayed in an innovative program for expanded telecom infrastructure, in which Grameen Bank (GB) of Bangladesh, the village-based micro-finance organization, leased cellular mobile phones to successful members. GB calls these phones Village Pay Phones (VPPs). The effects of VPPs are assessed from two angles:sellers of services (telephone lessees/owners) and buyers of services (villagers). The findings of the study lead to two basic conclusions: first, pursuance of pragmatic policies can turn telephones into production goods, especially through lowering transaction costs, and second, the services originating from telephones in villages are likely to deliver significant benefits to the poor. VPPs also seems to have perceptible and positive effects on the empowerment and social status of phone-leasing women and their households. For villagers in general, phones offer additional non-economic benefits such as improved law enforcement, more rapid and effective communications during disasters, stronger kinship bonding, etc. GB's style of managing communications can help significantly to expand access to this vital information input for all segments of the population, reduce inequality and thus enhance the broad-based, pro-poor orientation of rural development activities.